The Role of Parents in Cultivating the Religious Character of Elementary School Age Children During the Covid-19 Pandemic: Peran Orang Tua Dalam Menumbuhkan Karakter Religius Anak Usia Sekolah Dasar Pada Masa Pandemi Covid-19 - Novia Cahya Istiana; Feri Tirtoni (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to find out what the role of parents is in cultivating the religious character of elementary school age children during the COVID-19 pandemic and to find out what the religious character of grade 4A students at SDN JEPARA 1/90 is like. This research uses descriptive qualitative research with case studies. This study uses interview techniques, questionnaires, and documentation. The subjects studied in this study were 5 guardians and 5 students in grade 4A. The results of this study are parents act as role models and motivators for children, and the religious character of grade 4A students at SDN JEPARA 1/90 has shown indicators of obedience to Allah SWT, sincerity, responsibility and tolerance.